Relationship between market and institutional networks and technological innovation: an analysis of peruvian manufacturing firms - Del Carpio Gallegos, Javier Fernando (2021)
Firms strive to develop technological innovations. This study focuses on two main objectives: to identify the relationship between market and institutional networks and technological innovation; and to analyze the relationship between the obstacles that firms assess when developing innovations. The literature shows that there has been little interest in researching innovation in emerging economies, in which there is a greater presence of low-technology intensity firms that also develop technological innovations. Using data from 705 Peruvian manufacturing firms, a partial structural equation model was applied. The results showed that when firms are linked to networks, their capacity for technological innovation improves.